Properties of concrete containing POFA with different fineness as partial sand replacement - Nur Azzimah, Zamri (2012)
Malaysia is the world largest exporters of palm oil which the industry has brought enormous revenue to our country. However, palm oil fuel ash which is a by product from palm oil mill that has been dumped at landfill thus causing environmental pollution. It is seen that incorporation this Waste in concrete production would be able to reduce amount of waste disposed at landfill. This investigation focus on the effect of POFA fineness on the workability, compressive strength and moisture absorption of concrete. Plain concrete is used as control specimen.. Another type is concrete mix containing POFA of different fineness which replace 10 % POFA of sand by weight. The POFA was sieve into several of fineness that are POFA passing 300 pm, POFA passing 600 pm, POFA passing 1.18 mm and POFA originally taken from palm oil mill. The results revealed that the workability is the highest when using smallest particle of POFA that is POFA passing 300 pm. For compressive strength, it shows that POFA concrete are much lower than that of concrete without POFA. Mix containing POFA passing 300 tm recorded highest in strength compare to those POFA concretes at 28 days. In the case of water absorption, POFA passing 1.18 mm recorded the highest water absorption compare to other POFA concretes. Thus, it is recommended that POFA passing 300 gm can be added as partial sand replacement to produce concrete.